2019
DOI: 10.1063/1.5098533
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the surface species during temperature dependent dehydrogenation of naphthalene on Ni(111)

Abstract: The temperature dependent dehydrogenation of naphthalene on Ni(111) has been investigated using vibrational sum-frequency generation spectroscopy, X-ray photoelectron spectroscopy, scanning tunneling microscopy, and density functional theory with the aim of discerning the reaction mechanism and the intermediates on the surface. At 110 K, multiple layers of naphthalene adsorb on Ni(111); the first layer is a flat lying chemisorbed monolayer, whereas the next layer(s) consist of physisorbed naphthalene. The arom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 63 publications
(81 reference statements)
3
13
0
Order By: Relevance
“…We assume that to be the best model of the surface chemistry, i.e., at different temperatures, we have a complex mix of C fragments with varying degrees of dehydrogenation and a range of changing BEs rather than a mixture of naphthalene and graphitic carbon with changing relative amounts. This is consistent with the wide temperature range of hydrogen production observed in the TPD spectra previously. , …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…We assume that to be the best model of the surface chemistry, i.e., at different temperatures, we have a complex mix of C fragments with varying degrees of dehydrogenation and a range of changing BEs rather than a mixture of naphthalene and graphitic carbon with changing relative amounts. This is consistent with the wide temperature range of hydrogen production observed in the TPD spectra previously. , …”
Section: Resultssupporting
confidence: 92%
“…For mechanistic studies, representative tar components are often chosen as model compound. A good choice is naphthalene, which has been shown to be harder to decompose in thermal and catalytic steam reforming than other tar compounds. , The reaction of naphthalene on Ni(111) was studied by our group using surface science techniques. , It was found that on clean Ni(111), in the absence of an oxidant, naphthalene decomposes on the surface via dehydrogenation, which can be observed in two main H 2 desorption peaks at 450 and 600 K . Carbon remains on the surface at temperatures up to 700 K, as graphitic and carbidic carbon, and leads to a passivation of the surface after repeated adsorption/desorption cycles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, this peak vanishes in the partially deuterated carbaryl- d 7 SFG spectrum due to the absence of C–H aromatic contributions, in direct agreement with the spectral assignment and ruling out NH vibrational modes or high-frequency methyl antisymmetric stretches. This dominant SSP contribution of carbaryl at ∼3055 cm –1 is also in agreement with the sharp resonance observed at 3057 cm –1 in vSFG studies of naphthalene films. , The unique relative polarization-dependent intensity of the C–H stretching aromatic band in the carbaryl spectrum will be used to determine the orientation of the carbaryl naphthyl ring at the air/solid interface.…”
Section: Resultssupporting
confidence: 82%
“…This dominant SSP contribution of carbaryl at ∼3055 cm −1 is also in agreement with the sharp resonance observed at 3057 cm −1 in vSFG studies of naphthalene films. 92,93 The unique relative polarization-dependent intensity of the C−H stretching aromatic band in the carbaryl spectrum will be used to determine the orientation of the carbaryl naphthyl ring at the air/solid interface.…”
Section: ■ Introductionmentioning
confidence: 99%